2002
DOI: 10.1126/science.1067568
|View full text |Cite
|
Sign up to set email alerts
|

Brain to Plasma Amyloid-β Efflux: a Measure of Brain Amyloid Burden in a Mouse Model of Alzheimer's Disease

Abstract: The deposition of amyloid-beta (Abeta) peptides into amyloid plaques precedes the cognitive dysfunction of Alzheimer's disease (AD) by years. Biomarkers indicative of brain amyloid burden could be useful for identifying individuals at high risk for developing AD. As in AD in humans, baseline plasma Abeta levels in a transgenic mouse model of AD did not correlate with brain amyloid burden. However, after peripheral administration of a monoclonal antibody to Abeta (m266), we observed a rapid increase in plasma A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
364
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 528 publications
(404 citation statements)
references
References 16 publications
34
364
0
3
Order By: Relevance
“…For example, recent studies in a mouse model of stroke showed that HUCBC transplantation results in significant reduction in the infarct volume as well as rescue of neurological deficits associated with decreased production of proinflammatory cytokines [7]. We previously showed that HUCBC (95%-98% mononuclear cells) infusion could impact Ab-associated pathology in PSAPP mice [38]. It has been shown that Ab peptides mediate proinflammatory and neurodegenerative changes and oligomeric forms of the peptide are neurotoxic as well as synapse toxic [39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies in a mouse model of stroke showed that HUCBC transplantation results in significant reduction in the infarct volume as well as rescue of neurological deficits associated with decreased production of proinflammatory cytokines [7]. We previously showed that HUCBC (95%-98% mononuclear cells) infusion could impact Ab-associated pathology in PSAPP mice [38]. It has been shown that Ab peptides mediate proinflammatory and neurodegenerative changes and oligomeric forms of the peptide are neurotoxic as well as synapse toxic [39].…”
Section: Discussionmentioning
confidence: 99%
“…After a peripheral administration of a monoclonal antibody to Ab in mice, a rapid increase in plasma Ab was observed that is highly correlated with the amyloid burden in the brain [85]. If a similar phenomenon is observed in humans, such an antibody may be useful for quantifying brain amyloid burden in patients who have been diagnosed with Alzheimer's disease, or even known to be at risk of developing it.…”
Section: Diagnostic Reagentsmentioning
confidence: 92%
“…Non-Fc-mediated mechanisms may be involved in clearance of A␤ plaques because F(abЈ) 2 fragments that lack the Fc region of the antibody also are effective . Another proposed mechanism of A␤ clearance is that the site of antibody action is in the periphery, where the anti-A␤ antibodies would sequestrate soluble forms of A␤ in the peripheral circulation and drive an efflux of A␤ from the brain to the blood plasma, providing a "peripheral sink" for A␤ clearance (DeMattos et al, 2001(DeMattos et al, , 2002aLemere et al, 2003). This hypothesis was proposed based on data on passive transfer of an anti-A␤ monoclonal antibody (mAb) 266, which recognizes the midportion of A␤ and has a high affinity to soluble A␤ but not to aggregated ␤-amyloid (Seubert et al, 1992;DeMattos et al, 2001), in PDAPP Tg mice.…”
Section: Introductionmentioning
confidence: 99%